Touch-Screen Computerized Quality-of-Life Assessment for Patients with Cancer - Eun-Hyun Lee, PhD, RN (Elsevier, 2009)
To evaluate a computerized self-reported, touch-screen version of the cancer-specific quality-of- life (cC-QOL) questionnaire against the traditional paper-and-pencil version (the pC-QOL) for equivalence, time for completion, user preference and ease of use. Methods: One hundred and five patients were recruited from a cancer center of a university hospital in South Korea. A randomized crossover design was used, with patients randomly assigned into two groups. Group A patients completed the cC-QOL first while waiting to see a physician, and completed the pC-QOL version of the questionnaire after seeing the physician. Group B patients completed these questionnaires in the reverse order. Subjects were asked about user preference and ease of use. Time taken to complete both versions was measured. Results: Weighted kappa coefficients of items showed very good to moderate agreement. The time required to complete the cC-QOL did not differ statistically from the pC-QOL. The same proportion of patients preferred both versions. Most patients (94.8%) reported that the cC-QOL was "easy" or "very easy" to complete. Conclusion: The cC-QOL is the computerized equivalent of the pC-QOL, which is used to assess the health-related quality of life (HRQOL) of cancer patients. The cC-QOL can be helpful to oncology nurses and physicians for assessing, collecting, and evaluating their patients' HRQOL scores in busy clinical practices. [Asian Nursing Research 2009;3(1):41-48]